2019
DOI: 10.21037/cdt.2019.02.02
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity: an emerging problem in patients with congenital heart disease

Abstract: Due to technological and medical advances the population of adults with congenital heart disease (ACHD) is constantly growing. Worldwide, congenital heart disease (CHD) affects 1.35-1.5 million children each year and the number of ACHD meanwhile exceeds the number of CHD children. It has been found that a substantial number of ACHD present problematic health behaviors, such as physical inactivity and bad nutritional habits. Recent studies document alarming rates of overweight and obesity among CHD patients whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Many literature studies extensively identified that either irregular physical exercise or physical inactiveness [7,10,14,15,26,30], watching television or prolonged screen time [27,30], short sleep duration or shift work [15,24,30], stress, obesogenic environment (urbanization and industrialization) [31], smoking [10], and frequent use of a taxi for transportation [10,32] were determinant factors for overweight/obesity.…”
Section: Behavioral Factors (Feeding Habit and Life Style)mentioning
confidence: 99%
See 1 more Smart Citation
“…Many literature studies extensively identified that either irregular physical exercise or physical inactiveness [7,10,14,15,26,30], watching television or prolonged screen time [27,30], short sleep duration or shift work [15,24,30], stress, obesogenic environment (urbanization and industrialization) [31], smoking [10], and frequent use of a taxi for transportation [10,32] were determinant factors for overweight/obesity.…”
Section: Behavioral Factors (Feeding Habit and Life Style)mentioning
confidence: 99%
“…A review conducted in the USA population shows that the magnitude of obesity among coronary heart disease patients was increased [31]. e effect of obesity varies in different age groups; a systematic review identified that students with obesity in tertiary education have low academic performance and poor achievements either due to weight gain bias stigma or metabolic disorder [67].…”
Section: Health Impact Of Obesitymentioning
confidence: 99%
“…Health care for ACHD should encompass patient education as part of their disease management, individually adapted to the patients' medical counselling needs. There is increasing evidence that many ACHD need support concerning psychological difficulties, dietary patterns, and exercise capacity in their daily life (35,42,43). Therefore, it is of particular importance to individually advise ACHD on these demanding issues in order to prevent a high proportion of comorbidities that could be caused by unhealthy lifestyle habits, and to give ACHD the chance to take more responsibility in their own lives (44).…”
Section: Future Aspects Of Medical Care For Achdmentioning
confidence: 99%
“…9 Concerns have been raised about the increased risk of being overweight and having additional cardiometabolic disease later in life in patients with CHD and the risk is even higher with more severe CHD. [10][11][12] Due to limitations in physical capacity, 6,7 but also because of restrictions from parents and caregivers and low selfefficacy, 8,13 it may be assumed that children and adolescents with CHD are less physically active than children and adolescents in general. This creates a need to focus on aspects of health-related quality of life, physical activity, and prevention of acquired cardiovascular disease in this group of patients.…”
Section: Take Home Messagementioning
confidence: 99%